EPISTEMOLOGI FAZLUR RAHMAN DALAM MEMAHAMI ALQURAN DAN HADIS - M Samsul Ma'arif (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: Epistemology of Fazlur Rahman in Understanding the Qur’an and Hadith. This article  examines the epistemology of Fazlur Rahman in understanding the Qur’an and  the hadith,  and  was  his thought  of the qur’an  and  hadith  relevance to the  modern era.  This research is a library research, using  a hermeneutic approach or historical-critical approach. The collected datas  are analyzed  in descriptive-analytic. The results showed; Firstly, epistemology of Fazlur Rahman in understanding the Qur’an and the hadith  is epistemology of Burhani,  this epistemology is based on observation and  experimentation which  is systematized with the operationalization of the methods of historical  criticism,  sistematic interpretation and refined  by the method of double movement. While the arguments reasoning used  in understanding the Qur’an and  the hadith  is a demonstrative argument, verification and exploratory with a historical approach, normative and philosophical. Secondly, epistemology of Fazlur Rahman has significant relevance to the development of qur’anic and hadith thought  in the  modern era,  mainly in the  aspect of development and  methodology system.  However,  with regard  to the evolution  of the sunna and  the hadith,  although it has defended his entity from the orientalist, Fazlur Rahman has  a conception of liberal and  dangerous, because he  doubted the  validity of most  of the traditions  of the  technical contained in the  books  of hadith,  he thought  that the  itsnad  does  not ensure the validity of the hadith, because itsnads  itself is emerging at the end of the first century  AH.